Nova Britannia : offering most excellent fruites by planting in Virginia : exciting all such as be well affected to further the same - Johnson, Robert, active 1586-1626 (LLMC-digital (Series), 1609)
A booklet entitled "Nova Britannia: Offerning most excellent fruites by planting in Virginia," by Robert Johnson, and printed in London in 1609. This sermon included discussions of religion, colonization and increasing Britain's prestige.